MANAJEMEN PONPESMA UNISLA BERBASIS WEB - Agus Setia Budi; Nur Nafi’iyah (SPIRIT, 2018)
Management as a role is mentioned as administration, and management as a task is to carry out management functions. The notion of the need for management in the Unisla Ponpesma is seen as a necessity in order to survive in the midst of competition and globalization, as well as a foundation for future developments. Educational management has an important role in order that the Islamic boarding school can run effectively and efficiently in accordance with the goals set. PHP is a script used to create dynamic web pages. Dynamic means the page to be displayed is created when the page is requested by the client. This mechanism causes the information received by clients is always the latest or up to date. All PHP scripts are executed on the server where the script is run. MySQL can be defined as a database management system. The database itself is a data storage structure. To add, access and process data stored in a computer database, a database management system such as MySQL Server is required.Keywords : management system, Unisla Ponpesma, PHP, MySQL